1997
DOI: 10.1002/(sici)1096-8644(199703)102:3<301::aid-ajpa1>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Y chromosome markers and trans-Bering Strait dispersals

Abstract: Five polymorphisms involving two paternally inherited loci were surveyed in 38 world populations (n = 1,631) to investigate the origins of Native Americans. One of the six Y chromosome combination haplotypes (1T) was found at relatively high frequencies (17.8-75.0%) in nine Native American populations (n = 206) representing the three major linguistic divisions in the New World. Overall, these data do not support the Greenberg et al. (1986) tripartite model for the early peopling of the Americas. The 1T haploty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
3
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 33 publications
5
71
3
1
Order By: Relevance
“…Earlier, haplogroup Q1a3a has been discovered at a low frequency in Siberian Eskimos, Chukchi and Evens. 43,44 Karafet et al 43 have hypothesized that this haplogroup may have originated in the New World/eastern Beringia and that its infrequent presence in Northeast Siberian populations can be explained by back-migration from Alaska to Siberia. A search of Q1a3a-M3 STRhaplotypes revealed in Evens in the YHRD 3.0 database (http:// www.yhrd.org; release 36 built on 15 April 2011; 91 493 haplotypes within 686 world populations) has shown that matching haplotypes (for loci DYS19, DYS385a, DYS385b, DYS389I, DYS389II, DYS390, DYS391, DYS392 and DYS393) are rarely present in modern Native American populations.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, haplogroup Q1a3a has been discovered at a low frequency in Siberian Eskimos, Chukchi and Evens. 43,44 Karafet et al 43 have hypothesized that this haplogroup may have originated in the New World/eastern Beringia and that its infrequent presence in Northeast Siberian populations can be explained by back-migration from Alaska to Siberia. A search of Q1a3a-M3 STRhaplotypes revealed in Evens in the YHRD 3.0 database (http:// www.yhrd.org; release 36 built on 15 April 2011; 91 493 haplotypes within 686 world populations) has shown that matching haplotypes (for loci DYS19, DYS385a, DYS385b, DYS389I, DYS389II, DYS390, DYS391, DYS392 and DYS393) are rarely present in modern Native American populations.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that we could not test some rarely determined G3m allotypes, like G3m (26) and G3m (27), due to the lack of antisera, should be taken into account to clarify this ± ± ± ± Met ± ± ± ± ± g4 ± ± ± ± ± Arg Glu ± ± ± G3m 5,10,11,13,14 ± ± ± Ser Met ± ± Ile Arg Phe G3m 5,6,10,11,14 ± ± ± Ser Met ± Glu Ile Arg Phe G3m 5,6,11,24 ± ± ± Ser ± Arg Glu ± Arg Phe G3m 10,11,13,15 ± ± Met Ser ± ± ± Ile ± ± G3m 10,11,13,15,16 ± Trp Met Ser ± ± ± Ile ± ± G3m 21,28 Leu ± ± ± Met ± ± Ile Arg ± (10), (13), (14) allotypes in G3m 21,28 haplotypes, whereas non-expression of G3m (14) is probably associated to Val397 in G3m 5,6,11,24 , G3m 10,11,13,15 and G3m 10,11,13,15,16 haplotypes; d Non-expression of G3m (13) correlates with the expression of G3m (6) in G3m 5,6,10,11,14 and G3m 5,6,11,…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, all Selkup, Lebanese and French G3m 5,10,11,13,14 sequences (n=7) are identical to each other, except in the hinge region (S+L and L+F). The G3m 21,28 haplotype is also highly variable at the DNA level, as four distinct sequences are found among 10 G3m 21,28 genes, and the three G3m 21,28 sequences observed in the Selkups are different from each other (S+F, S1, S2). The sequences associated to haplotype G3m 10,11,13,15,16 vary among populations, as that found in Lebanese (L2, n=3) differ from that found in Selkups (S3, n=6) by one substitution.…”
Section: Dna Sequence Variability Of Ighg3 Genes P Dard Et Al 766mentioning
confidence: 99%
See 2 more Smart Citations